THE EFFECTS OF VOCABULARY MASTERY ON SPEAKING ABILITY IN VIEW OF COMMUNICATIVE COMPETENCE OF THE MA NW NURUL HAROMAIN GRADERS - mul muliadi (Lembaga Penelitian dan Pendidikan Mandala, 2018)
This research is aimed to measure the correlation between vocabulary mastery and the speaking ability. In this case, the effect of vocabulary mastery on speaking ability is seen as a cause and effect. Furthermore, this research is also intended to look further at how the vocabulary mastery affects the students’ speaking ability. Based on these facts, this research is categorized into descriptive research. The data of this research is collected through tests. There are 2 types of tests that have been given to measure the students’ ability in mastering vocabulary and speaking ability. Vocabulary test includes translating words (both into Indonesian and into English), and matching items. In doing speaking test, the researcher records the students’ performance when they present their oral test; the students are requested to stand in front of the class to speak about the certain topic for 3 to 4 minutes as the speaking test. The result presents that students’ speaking ability is much influenced by their vocabulary mastery. More than half students obtained high score both in mastering vocabulary test and speaking ability test. This is obvious that the vocabulary mastery plays an important role in speaking ability. Since the score obtained is high, it indicates that the students at MA NW Nurul Haromain , especially who have been as the subject of this research, have gained better achievement in speaking ability. Mastering vocabulary is one of the solutions for the learners to speak. Vocabulary mastery and speaking ability has close correlation each other since vocabulary is a branch of speaking skill. It is also a foundation to better speaking ability which has relationship to other language aspects.